2004
DOI: 10.1007/s00442-004-1492-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of conspecific alarm cues by juvenile salmonids under neutral and weakly acidic conditions: laboratory and field tests

Abstract: A variety of fishes possess damage-released chemical alarm cues, which play a critical role in the detection and avoidance of potential predation threats. Recently, we have demonstrated that the ability of fathead minnows ( Pimephales promelas) and finescale dace ( Phoxinus neogaeus) to detect and respond to conspecific alarm cues is significantly reduced under weakly acidic conditions (pH 6.0). Rainbow trout ( Oncorhynchus mykiss) and brook charr ( Salvelinus fontinalis) possess an analogous alarm cue system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 27 publications
8
64
0
Order By: Relevance
“…Experiments with freshwater fish have demonstrated a range of behavioural and ecological changes associated with the impairment of olfaction and chemical cues detection under weakly acidified conditions (approx. pH 6.0) [20,37,38]. Recently, a very similar range of behavioural changes has been observed in experiments with marine fish exposed to predicted future changes in ocean pH due to rising atmospheric CO 2 [39,40].…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Experiments with freshwater fish have demonstrated a range of behavioural and ecological changes associated with the impairment of olfaction and chemical cues detection under weakly acidified conditions (approx. pH 6.0) [20,37,38]. Recently, a very similar range of behavioural changes has been observed in experiments with marine fish exposed to predicted future changes in ocean pH due to rising atmospheric CO 2 [39,40].…”
Section: Introductionmentioning
confidence: 61%
“…These behavioural responses to alarm cues have been observed in a range of freshwater fishes, including fathead minnows (Pimephales promelas), finescale dace (Phoxinus neogaeus), pumpkinseed (Lepomis gibbosus) and rainbow trout (Oncorhynchus mykiss) [20,37,44]. However, predator avoidance behaviour was diminished or absent when these alarm cues were presented in experimental treatments acidified using a minute amount of sulfuric acid (often a major contributor to freshwater acidification) [20,38,45]. Furthermore, behavioural responses to basic chemical stimuli from food (amino acids) were significantly reduced under a similar range of pHs (e.g.…”
Section: Ecological Effects Of Acidification On Olfaction (A) Freshwamentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, exposure to acidic compounds can cause stress in fish if this falls below normal tolerance levels through gill and epidermal damage. This may lead to problems with osmoregulation and oxygen uptake (Branson, 1992) and changes in behaviour (Brown et al, 2012;Leduc et al, 2004). Reilly et al (2008) have previously reported that both zebrafish and rainbow trout show behavioural responses after subcutaneous injection of dilute acetic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Ocean acidification associated with increasing atmospheric concentration of carbon dioxide and acidification of lakes and streams by sulfur and nitrogen deposition are two well known examples. Chemoreception in fish (Smith and Lawrence 1988, Brown et al 2002, Leduc et al 2004) and crayfish (Allison et al 1992) is impaired in weakly acidified streams. Similarly, marine fish reared in acidified seawater fail to respond appropriately to predator cues (Dixson et al 2009).…”
Section: Introductionmentioning
confidence: 99%